Performance of pulsed-electrochemical honing and pulsed-electrochemical finishing in improving quality of bevel gears - Pathak, Sunil; Jain, Neelesh Kumar (EDP Sciences, 2018)
This article presents a comparative study concerning performance of pulsed-electrochemical honing (PECH) and pulsed-electrochemical finishing (PECF) in straight bevel gear finishing. Performance of these processes were compared in terms of average percentage difference in the considered parameters of surface features of bevel gear namely average percentage differences in average surface roughness ‘PDRa’, maximum surface roughness ‘PDRmax’ and depth of surface roughness ‘PDRz’, micro-geometry (i.e. average percentage differences in single pitch error ‘PDfp’, adjacent pitch error ‘PDfu’, cumulative pitch error ‘PDFp’, and percentage difference in runout ‘PDFr’) and finishing productivity (i.e. material removal rate ‘MRR’). Microstructure and microhardness were also considered as measure for performance assessment. Observed results show PECH is proficient in simultaneously improving all the considered responses of bevel gears by more than 50% as compared to PECF. The PECH-finished gear additionally displayed unrivalled microstructure and better microhardness when contrasted with PECF-finished gear. These changes will upgrade the working-life and operating performance of the finished gear.